1991
DOI: 10.2527/1991.693923x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of breed, number of suckling lambs, and stage of lactation on ewe milk production and lamb growth under range conditions.

Abstract: Milk production and lamb growth were characterized in 118 multiparous, 3- to 7-yr-old Rambouillet, Columbia, Polypay, and Suffolk ewes under spring sage range and high mountain meadow grazing from 28 to 98 d postpartum. Daily milk yield as measured by the lamb suckling weight differential technique did not differ (P greater than .05) among breeds, although milk production of Suffolk ewes tended to be higher than that of the other three breeds. Within the Rambouillet, Columbia, and Polypay breeds, total estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
2
11

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 4 publications
(5 reference statements)
8
58
2
11
Order By: Relevance
“…Ewes nursing single lambs presented higher average daily milk production (P<0.05), contrarily to the findings of Snowder & Glimp (1991), Ramsey et al (1998) and Cardellino & Benson (2002), who observed higher productions for ewes nursing twins.…”
Section: Resultscontrasting
confidence: 40%
“…Ewes nursing single lambs presented higher average daily milk production (P<0.05), contrarily to the findings of Snowder & Glimp (1991), Ramsey et al (1998) and Cardellino & Benson (2002), who observed higher productions for ewes nursing twins.…”
Section: Resultscontrasting
confidence: 40%
“…Os resultados obtidos são discordantes aos encontrados por Snowder & Glimp (1991), que verificaram alto teor de lactose aos 28 dias, com queda gradativa ao longo da lactação, conforme a produção diminuiu.…”
Section: Resultsunclassified
“…Porém, quando a produção de leite diminuiu, na décima primeira semana de lactação, a porcentagem de lactose do tratamento 2 (fotoperíodo longo) passou a ser menor (Figura 2). Snowder & Glimp (1991) observaram maior teor de lactose aos 28 dias, e redução do mesmo, ao longo da lactação. No que diz respeito aos sólidos totais, constatou-se uma relação inversa entre a produção e a porcentagem dos constituintes do leite.…”
Section: Resultsunclassified